Estado nutricional de los padres de familia y sus hijos escolares de la IEI 536 Mi Casita del Saber –San Juan Bautista, 2024 - Saavedra Amasifuen, Christhian Kervin (2024)
The objective of this study was to determine the relationship between the nutritional status of parents and the nutritional status of their school children at the IEI 536 My Little House of Knowledge – San Juan Bautista, 2024. The research had a descriptive correlational, non-experimental, quantitative approach with a cross- sectional approach. The sampling was a probabilistic census type. The population and sample consisted of 80 children from 3 to 5 years of age and 80 parents of both sexes. Anthropometric measurements and biochemical evaluations were carried out on children aged 3 to 5 years and parents. In school children, 12.50% had malnutrition according to the P/E indicator, 26.25% had short stature, 47.50% had malnutrition and 10.00% according to the P/T indicator. 30.00% and 38.75% mild and moderate anemia respectively. In parents, 67,505% were overweight according to BMI and 42.50% risk and 40.00% very high risk according to abdominal circumference. In addition, it found 20% mild anemia, 16.25 moderate anemia and 21.25% high glucose. It was concluded that there is a significant statistical relationship between the 4 indicators of the nutritional status of parents with anemia in children from 3 to 5 years of age. A statistical relationship was also found between parents' BMI and weight for age and body mass index for age. In addition, statistical anemia parents and anthropometric indicators.